Relationship Between Breastfeeding Duration and Exclusivity on Various Language Milestones in United States Children Aged 3–5 Years - Malika Goel; Sowmya Jayachandran; Sandhya J. Kadam; Rhythm Sharma (Children, 2025)
Background/Objectives: Breastfeeding has been positively associated with development of various developmental and cognitive outcomes. Although not fully understood, psychosocial, environmental, nutrients (docosahexaenoic acid) etc., have been proposed as reasons. There is a paucity of studies that have looked at individual language milestones and language milestones associated with school readiness in the age group of 3–5 years old in a nationally representative sample. This study aimed to analyze the language milestones association with breastfeeding in this group of children. Methods: The dataset was obtained from the National Survey of Child Health (NSCH) 2022–2023 combined sample. Overall, 22,866 children met the inclusion criteria. Secondary analysis of the NCSCH data was done using multinomial regression models amongst four breastfeeding categories (never breastfed, breastfed less than 6 months, breastfed until 6 months but not exclusively, exclusive breastfeeding) with 16 language variables. Results: The results of the study show that children in the breastfeeding categories (breastfed until 6 months but not exclusively and exclusive breastfeeding until 6 months) had a positive association across many language variables including variables used to analyze school readiness. Individual language variables’ adjusted odds ratio and significance has been analyzed. The reference category was never breastfed. Conclusions: The study results support positive association of breastfeeding with language variables. Per our review, limited research has been reported where so many individual language variables have been analyzed in a nationally representative sample across four different breastfeeding categories.